Identification of material properties of orthotropic composite plate using hybrid non-destructive evaluation approach. (8th December 2014) - Kong, K. K.; Ong, Z. C.; Khoo, S. Y.; Ismail, Z.; Ang, B. C.; Chong, W. T.; Noroozi, S.; Rahman, A. G. A.
<x content-type="archive" xml:space="preserve">Abstract</x> Identification of material properties is one of the key issues in composite materials research. The mechanical properties of composite materials depend on diverse factors such as configuration of the laminates, constituent materials used and production method adopted. Conventional testing approach tends to be time-consuming, expensive and destructive. As an alternative, a rapid, inexpensive, hybrid and non-destructive evaluation approach which utilises experimental modal analysis and finite element analysis is proposed. Experimental modal data which consist of natural frequencies and mode shapes of an orthotropic composite plate are utilised for correlation purpose with its finite element model. This finite element model of the composite plate is continuously updated and achieves less than 5% in difference of natural frequencies and over 70% in modal assurance criterion. Material properties such as Young's moduli, in-plane shear modulus and Poisson ratio of the composite plate are then successfully determined using the well-correlated FE model.